The Effectiveness of Combining Walking Exercise and Autogenic Relaxation on Blood Glucose Levels in Patients with Type II Diabetes Mellitus - Mia Yuliana; Beti Kristinawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Type II Diabetes Mellitus (DM) is a chronic metabolic condition that requires long-term treatment. Sedentary lifestyles and stress are the primary causes of its growing global prevalence. Non-pharmacological therapies, such as physical activity and relaxation techniques, can aid in blood glucose regulation. The purpose of this study is to evaluate the efficacy of combining walking exercise and autogenic relaxation in lowering blood glucose levels in Type II diabetic patients. A case study was conducted on a 50-year-old woman with type II diabetes mellitus for five years. The intervention combined walking exercise (30 minutes/session, three times a week) and autogenic relaxation (15–20 minutes/session, three times a week) for four weeks. Data were collected through interviews, observations, and glucometer measurements before and after the intervention. Data were analyzed by conducting a case study of nursing care. Fasting blood glucose levels fell from 500 mg/dL to 148 mg/dL, tiredness scores improved from 6 to 3, stress scores from 7 to 3, and exercise tolerance increased from 10 to 25 minutes of continuous walking. These findings suggest improved glycemic management, endurance, and psychological well-being. Combining walking exercise and autogenic relaxation is an effective, simple, and low-cost nursing intervention to support blood glucose control in Type II DM patients.